2001
DOI: 10.1097/00005131-200109000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of the Less Invasive Stabilization System for the Internal Fixation of Distal Femur Fractures

Abstract: These results suggest an enhanced ability to withstand high loads when using the monocortical screw fixation technique with angular stability. A higher elastic deformation of LISS compared with conventional plating systems in distal femoral fractures can be explained by the lower bending stiffness caused by different design and material properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(125 citation statements)
references
References 11 publications
2
115
0
5
Order By: Relevance
“…Even more, the mean axial stiffness of the AxSOS plate systems tested in our study is similar to that of AxSOS plate systems (110 N/mm) reported by Wähnert et al [20]. The loading regimen for axial loading used in our study is based on comparable testing methodologies used by other authors [14,20]. The incremental axial loading applied in these studies is considered representative of physiologic postoperative loading of the distal femur and based the results of in vivo telemetry studies [6,17,18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Even more, the mean axial stiffness of the AxSOS plate systems tested in our study is similar to that of AxSOS plate systems (110 N/mm) reported by Wähnert et al [20]. The loading regimen for axial loading used in our study is based on comparable testing methodologies used by other authors [14,20]. The incremental axial loading applied in these studies is considered representative of physiologic postoperative loading of the distal femur and based the results of in vivo telemetry studies [6,17,18].…”
Section: Discussionsupporting
confidence: 81%
“…Our fracture model represents an extraarticular fracture, which is classified as a type of distal femur fracture [15] associated with substantial complication rates [16]. This model is used in multiple biomechanical studies [5,11,14,21,25]. The fracture model used in our study with a fracture gap of 25 mm may not correlate with the clinical fracture pattern; however, it was created to perform a worst case fracture pattern without any inherent stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the fixed connection between screws and plate promotes stability in the system, the higher caliber of LISS® screws leads to a better load distribution. Both factors lead to a lower rate of secondary loosening and screw dislocation [7]. Especially in osteoporotic bones these advantages account for higher stability and reduction of secondary dislocation [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Introduzia-se, assim, o conceito de implantes que atuavam como fixadores externos, mas aplicados bem próximo ao osso: os fixadores internos (6)(7)(8) . Os fixadores internos, assim como os externos, asseguravam algum grau de movimento no foco de fratura, agindo pelo princípio da estabilidade relativa e levando à consolidação mediante a formação de calo ósseo (9) .…”
Section: Introductionunclassified